(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Thalassemia is a type of inherited blood disorder characterised by red blood cells (erythrocytes) that are easily damaged or have a shorter lifespan than normal blood cells, which is 120 days. This condition is passed on by parents to their children since the womb. Knowledge about Thalassemia plays a very important role in Thalassemia prevention programmes in the community. Providing education on the genetic and inherited nature of Thalassemia, as well as carrier cases in the community is essential. Knowledge about the early symptoms of Thalassemia and screening behaviour as an effort to break the chain of Thalassemia needs to be given early on as a provision for the future in deciding to choose a life partner. The purpose of community service is to empower peers as educators in improving understanding of Thalassemia and screening behaviour. This activity was given to 75 students at SMA Negeri Kota Tasikmalaya who are members of the UKS and OSIS administrators. The method used in providing education was lecture with audiovisual media. The results of providing education showed an increase in the level of knowledge of students after health education compared to before, the average pretest score was 80.77 and the average posttest score was 91.07. The provision of education is expected to continue to be carried out with interesting methods so as to increase the knowledge and efforts of adolescents in preventing thalassaemia early on.